DINAMIKA PRESIDENTIAL THRESHOLD DALAM KODIFIKASI REGULASI PEMILU SERENTAK 2019 (Lex Jurnalica, 2019)
Article 6 and Article 6A of the 1945 Constitution of the Republic of Indonesia (URI NRI 1945) governs the nomination of the President, the provisions of which can be seen in Chapter III concerning the Power of State Government. Although there is a codification, the implementation of the election is not yet simple and easy. The method used in this research is normative juridical research. The threshold for nominating the President and Vice President which sets the threshold with the requirement to obtain a seat of at least 20% (twenty p ercent) of the total number of DPR seats or 25 (twenty-five percent) of the valid votes nationally in the previous DPR member elections contrary to the provisions of Article 22E Paragraph (2) of the 1945 Constitution. The threshold for nominating a president and vice president who sets a threshold with the requirement to obtain a seat of at least 20% (twenty percent) of the total number of seats in the DPR or 25 (twenty-five percent) of valid national votes on the previous DPR member election resulted in little room for the people to make their choice.